Word of Mouth or Online Services: What is the Best Determinant of Muzakki’s Preference in Selecting Zakat Agency? - Pusparini, Martini Dwi; Zahroh, Nur Azizah Zuhriah (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
The number of national-level zakat institutions has decreased since the implementation of Zakat Law Number 23 of 2011, indicating a more organized zakat administration. Nevertheless, many muzakki still opt not to distribute their zakat through the existing Zakat Management Organizations (OPZ) in Indonesia. Instead, they prefer to directly give zakat to their chosen mustahik. Despite the importance of paying zakat through zakat institutions, it is crucial to comprehend individuals' preferences in this regard. The main objective of this study is to investigate the factors influencing muzakki's preferences for zakat institutions, including trust, word of mouth, and online services. The research is based on empirical data gathered from 132 respondents in Central Java. Multiple linear regression was employed to test the study hypotheses. The findings reveal that all the examined variables, namely trust, word of mouth, and internet services, significantly influence muzakki's choices for zakat institutions. Further analysis indicates that among these factors, online services play the most significant role in shaping muzakki's preferences. The limitation of the study lies in the research sample, where Indonesia consists of 34 provinces and only 1 province is involved in this study. This study presents a summary of the relevance of online services in zakat institutions, as previous research on muzakki preferences for zakat payment has never included the online service factor. This research has managerial implications, particularly for Zakat Institutions. The findings will further assist fundraising strategies to enhance financial service and introduce innovative approaches to reach muzakki preferences in zakat payment.